Optimizing the kidney donor pool: transplanting donor kidneys after partial nephrectomy of masses or cysts - Tabbara, Marina M.; Riella, Juliano; Gonzalez, Javier; Gaynor, Jeffrey J.; Guerra, Giselle; Alvarez, Angel; Ciancio, Gaetano (Frontiers in Surgery, 2024)
Background A limiting factor in expanding the kidney donor pool is donor kidneys with renal tumors or cysts. Partial nephrectomy (PN) to remove these lesions prior to transplantation may help optimize organ usage without recurrence of malignancy or increased risk of complications. Methods We retrospectively analyzed all recipients of a living or deceased donor graft between February 2009 and October 2022 in which a PN was performed prior to transplant due to the presence of one or more concerning growths. Donor and recipient demographics, perioperative data, donor allograft pathology, and recipient outcomes were obtained. Results Thirty-six recipients received a graft in which a PN was performed to remove suspicious masses or cysts prior to transplant. Majority of pathologies turned out to be a simple renal cyst (65%), followed by renal cell carcinoma (15%), benign multilocular cystic renal neoplasm (7.5%), angiomyolipoma (5%), benign renal tissue (5%), and papillary adenoma (2.5%). No renal malignancy recurrences were observed during the study period (median follow-up: 67.2 months). Fourteen complications occurred among 11 patients (30.6% overall) during the first 6mo post-transplant. Mean eGFR (± standard error) at 36 months post-transplant was 51.9 ± 4.2 ml/min/1.73 m2 (N = 23). Three death-censored graft losses and four deaths with a functioning graft and were observed. Conclusion PN of renal grafts with suspicious looking masses or cysts is a safe option to optimize organ usage and decrease the kidney non-use rate, with no observed recurrence of malignancy or increased risk of complications.